Minimizing Voltage Losses in Perovskite Solar Cells. Issue 1 (6th October 2020) - Chen, Peng; Bai, Yang; Wang, Lianzhou
Abstract : Organic–inorganic metal halide perovskite solar cells (PSCs) have achieved an unprecedented increase in power conversion efficiency (PCE) from 3.8% to 25.2% in the past decade. Given that the open‐circuit voltage ( V oc ) of PSCs is well below its theoretical limit due to the trap‐mediated charge recombination and energy band alignment mismatch, there is still considerable scope to further increase the PCE by minimizing V oc losses. Herein, a fundamental understanding on the origins of voltage losses in PSCs is summarized. Then, the strategies for mitigating the voltage losses of PSCs are critically reviewed, including crystal growth control, grain‐boundary defect passivation, interfacial defect passivation, and band alignment optimization. Finally, the current challenges are discussed and the future directions are outlined to further boost the V oc of PSCs toward their radiative limit. Abstract : The open‐circuit voltage losses of perovskite solar cells (PSCs) mainly come from defect‐assisted nonradiative recombination and band alignment mismatch. In this review, promising strategies and future research opportunities for minimizing voltage losses of PSCs are overviewed in terms of bulk crystal, grain boundary, and interfacial defect passivation and band alignment optimization.